2018
DOI: 10.1097/gme.0000000000001079
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal estrogen and mammogram results: case series and review of literature on treatment of genitourinary syndrome of menopause (GSM) in breast cancer survivors

Abstract: Low-dose vaginal estrogen use for 1 or more years in a small cohort of women with GSM did not appear to be associated with any changes in breast density or Bi-RADS breast cancer risk scores in the majority of study participants, including three breast cancer survivors. Larger long-term controlled clinical trials should be conducted to examine the effects of low-dose vaginal estrogen on mammographic density in women with and without a personal history of breast cancer. Furthermore, relative efficacy and risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In one small, single-institution study of 20 postmenopausal patients, of whom three had a history of breast cancer, the authors found no new cancer or cancer recurrence after at least 1 year of vaginal estrogen use. 19 A large nested case-control study found no increased relative risk of cancer recurrence with the use of local estrogen during concurrent use of tamoxifen or aromatase inhibitors or after treatment with these medications. 20 A recent Danish cohort study of 8,461 women described no increased risk of recurrence or mortality in postmenopausal women with a history of early-stage breast cancer after treatment with vaginal estrogen therapy or menopausal hormone therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In one small, single-institution study of 20 postmenopausal patients, of whom three had a history of breast cancer, the authors found no new cancer or cancer recurrence after at least 1 year of vaginal estrogen use. 19 A large nested case-control study found no increased relative risk of cancer recurrence with the use of local estrogen during concurrent use of tamoxifen or aromatase inhibitors or after treatment with these medications. 20 A recent Danish cohort study of 8,461 women described no increased risk of recurrence or mortality in postmenopausal women with a history of early-stage breast cancer after treatment with vaginal estrogen therapy or menopausal hormone therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These studies included women taking tamoxifen and women taking AIs and had varied follow-up time. Additionally, no change in breast density or Bi-RADS scores was observed in a cohort study of menopausal women after 1 year of estrogen use (53).…”
Section: Hormonal Treatment Optionsmentioning
confidence: 99%